PENGARUH LITERASI PESERTA DIDIK TERHADAP MUTU SEKOLAH DI SD MUHAMMADIYAH CONDONGCATUR - Vinda Ayu Pratama Ayu; Siti Maisaroh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of literacy on school quality at SD Muhammadiyah Condongcatur. This research uses a quantitative approach with simple linear regression analysis. The research subjects consist of 30 students selected using a random sampling technique. Data collection was carried out through a 1-5 Likert scale questionnaire measuring two variables, namely literacy as the independent variable and school quality as the dependent variable. Data analysis was performed using simple linear regression. The results of this study showed that the coefficient value is 0.719 and the significance value (sig) is 0.230 (> 0.05). This shows that there is no significant influence of literacy on the quality of schools at SD Muhammadiyah Condongcatur. Therefore, literacy does not affect the quality of education. However, it is also influenced by other factors such as school management, teacher competence, facilities and infrastructure, and parental involvement in the education process.